2020
DOI: 10.1108/rpj-12-2019-0312
|View full text |Cite
|
Sign up to set email alerts
|

An experimental methodology to analyse the structural behaviour of FDM parts with variable process parameters

Abstract: Purpose This paper aims to investigate the structural behaviour of polylactic acid (PLA) parts fabricated by fused deposition modelling (FDM) to support the development of analytical and numerical models to predict the structural performance of FDM components and categories of similar additive manufactured parts. Design/methodology/approach A new methodology based on uniaxial tensile tests of filaments and FDM specimens, infill measurement and normalization of the results is proposed and implemented. A total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 21 publications
0
18
0
1
Order By: Relevance
“…The result indicated that the raster angle does not have a significant influence on the mechanical behavior of vertical specimens, but the parallel specimens still show a higher ultimate tensile strength (UTS). Sedighi et al and Cerda-Avila [ 17 , 18 ] both researched the mechanical properties of PLA material in different inner structures that resulted from different printing angles and build orientations. Similar results indicated that the filament arrangement in the specimens that was more parallel to the direction of the tensile load resulted in a higher tensile strength.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The result indicated that the raster angle does not have a significant influence on the mechanical behavior of vertical specimens, but the parallel specimens still show a higher ultimate tensile strength (UTS). Sedighi et al and Cerda-Avila [ 17 , 18 ] both researched the mechanical properties of PLA material in different inner structures that resulted from different printing angles and build orientations. Similar results indicated that the filament arrangement in the specimens that was more parallel to the direction of the tensile load resulted in a higher tensile strength.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Another main reason to cause those defects is the residual stress generated by the uneven temperature distribution. Numerous studies [20][21][22][23] have been conducted to investigate how the residual stress affects the final quality of the printed parts.…”
Section: Background and Related Workmentioning
confidence: 99%
“…Avila vd. [11] EYM ile Polilaktik asit (PLA) malzemeden üretilen yapılarda üretim yönünün, katman kalınlığının ve doluluk oranının yapıların mekanik özelliklerine etkisini incelemişlerdir. Gohar vd.…”
Section: Introductionunclassified